Evaluation of Natural Light in EcoHouse Bandung - Sutanty, Prisca Bicawasti Budi; Stefanus Christian Diyaneswara (Journal of Artificial Intelligence in Architecture, 2024)
The availability of natural lighting is significant to the quality of life in a residential setting. A residence that is conducive to health and comfort requires adequate natural sunlight, which can eliminate viruses and mould indoors and improve the health of its occupants. Furthermore, the strategic incorporation of natural lighting can also lead to a reduction in energy expenditure. This research aims to evaluate the natural lighting in the EcoHouse Bandung, designed by SHAU Architecture and Urbanism, to ascertain its effectiveness and identify areas requiring improvement. The methodology employed entails the utilisation of simulations conducted with the Autodesk Ecotect Analysis 2011, encompassing the assessment of Shadow Range, Solar Access Analysis, and Lighting Analysis. The analysis results demonstrate that the EcoHouse Bandung has responded effectively regarding orientation and building envelope utilisation. However, some areas require specific adjustments due to insufficient or excessive light intensity. The analysis indicates the necessity for optimisation in several areas, including workspaces, living rooms, dining rooms, and bathrooms on the first floor. This research identifies three main principles for eco-house design: firstly, primary lighting should not disturb neighbours or cause harm to occupants; secondly, facade materials and technologies should be selected based on each façade's specific requirements; and thirdly, corridors should be considered as primary barriers in reducing excess heat and light. These findings are anticipated to optimise existing conditions and achieve ideal standards that support environmental sustainability and occupant comfort.